"Wenn wir sagen, dass der Tropfen Mensch wird" Vorstellungen ungeborenen Lebens bei Bar ʿEbrāyā (1226-1286 n. Chr.) - Jäckel, Florian (Recht, Ethik und Gesellschaft im Vorderen Orient | Law, Ethics and Society in the Middle East, 2022)
Notions of the unborn can be found in diverse medical, philosophical and theological works from antiquity to the present. While prior studies have examined similarities and differences between such notions in various learned and religious contexts, Syriac literary tradition has hardly received any attention. This book is a sub-stantial contribution to closing this gap in research and to the cross-cultural history of philosophy. It analyses several key works in the corpus of the prolific polymath Bar ʿEbrāyā and traces his incorporation of Greek philosophical, Christian and Islamic texts into a novel 'embryological synthesis'.